(untitled) (Global Journal of Medical Research, 2022)
Drawing on the knowledge accumulated by the ancient Greek philosophers, medieval Arabic theoretical anatomy seeks to describe the organs, their roles and functions as well as their mutual relationships, embedding this description within a philosophical framework wherever higher or subordinate roles can be ascribed to the particular organs being discussed. According to Ibn Sīnā (Abū ’Alī al-Ḥusayn b. ’Alī)(Avicenna) (370-428 AH/980-1037 AD), everything in nature is connected with everything else, and the main operator of the body is the immortal divine soul (rūḥ). In the process of breathing, a part of the divine soul enters the lungs and then, being mixed with blood, the heart as well, in which the ’pneuma’ is formed, which is channeled by the arteries throughout the body. The soul part of the inhaled air (al-hawāʼ) regulates the heart’s heat and nourishes it. According to Ibn Sīnā, the heart has three cavities: one on the right side, one on the left side, and the third in the middle, which serves as a kind of blood store. The liver governs the right side, the spleen governs the left one.